2002
DOI: 10.1200/jco.2002.08.081
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Chemotherapy in the Treatment of Relapsed Osteosarcoma: An Italian Sarcoma Group Study

Abstract: HDCT combined with surgery is feasible and can induce CR in a large portion of patients. Two points, however, need to be considered: only patients who are chemosensitive to induction treatment can obtain CR after HDCT, and the length of remission is short, because most patients relapse. Thus novel strategies are needed to maintain the remission status or to treat patients who do not respond to induction treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
80
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(83 citation statements)
references
References 38 publications
2
80
0
1
Order By: Relevance
“…Patients who received standard chemotherapy before and after surgery and then radiation had the 5-year survival rate of 60-70% (Sampson et al 2015). Moreover, patients with metastatic and advanced tumors have only 23 months of median survival time (Fagioli et al 2002). Current clinical trials have not improved the overall survival of osteosarcoma patients, and the understanding of molecular pathogenesis of osteosarcoma is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Patients who received standard chemotherapy before and after surgery and then radiation had the 5-year survival rate of 60-70% (Sampson et al 2015). Moreover, patients with metastatic and advanced tumors have only 23 months of median survival time (Fagioli et al 2002). Current clinical trials have not improved the overall survival of osteosarcoma patients, and the understanding of molecular pathogenesis of osteosarcoma is limited.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Although methotrexate, doxorubicin, cisplatin and ifosfamide were shown to be active agents in osteosarcoma, their uses in high doses are limited owing to their toxicities. 11 However, high doses of etoposide and carboplatin have been shown to have antitumor effect with suitable toxicity profiles.…”
mentioning
confidence: 99%
“…11 However, high doses of etoposide and carboplatin have been shown to have antitumor effect with suitable toxicity profiles. 9,12 Previous studies on HDCT and ASCT in osteosarcoma used heterogeneous conditioning regimens and showed varying outcomes. 3,13,14 The current analysis of high-risk osteosarcoma patients treated with HDCT and ASCT with a uniform conditioning regimen MEC at our institute showed promising results.…”
mentioning
confidence: 99%
“…3,4,5 The tumor necrosis rate may be increased by multiple drug combinations, whereas HDC is found to be the most effective way of increasing the response rate among other conventional therapy modalities. HDC and APBSCT were reported previously to be used predominantly in metastatic osteosarcoma 7,8 and in various bone tumors with a poor prognosis. 9 In the current study, we examined the feasibility of HDC in patients with nonmetastatic, high-grade osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Hovewer, peripheral blood stem cell support can decrease the myelosupressive toxicities in several tumors, including sarcomas. 6 High-dose chemotherapy (HDC) and autologous peripheral blood stem cell support or transplantation (APBSCT) were reported to be the dominant modalities used in patients with metastatic osteosarcoma 7,8 and various bone tumors with poor prognosis. 9 In the current study, we planned to harvest and transplant PBSC after two cycles of an induction chemotherapy regimen.…”
mentioning
confidence: 99%